Influence Analysis of Lateral Connection between Track Beams of Suspended Monorail Transit Large-Span Bridges - LIU Yangming (Chengshi guidao jiaotong yanjiu)
［Objective］ Generally, the left and right track beams of suspended rail transit work independently, and are only connected at the piers. The track beams in mid-span are not connected to each other, which has little effect on small-span track beams. However, when there are large-span track beams, due to their small cross-section and weak stiffness, whether there is a lateral connection between the two track beams of the main span will greatly affect the dynamic response of the system. In this regard, it is necessary to analyze the influence of the lateral connection between track beams in suspended monorail transit large-span bridges. ［Method］ In order to explore the influence of different transverse beams in the bridge main span on the dynamic response and driving comfort of the suspended monorail transit system, based on Ansys finite element software and Universal Mechanism multi-body dynamics software, an 80 m long flexible suspender arch bridge and vehicle model is established for joint simulation calculation. The cross-sectional form of the transverse beam between track beams，and the dynamic response of the system under working conditions with 0, 1, and 3 transverse beams on the midspan left and right sides are analyzed. ［Result & Conclusion］ The lateral stiffness of the transverse beam section of the track beam has little contribution to the longitudinal displacement of the track beam, but the ability of transverse beam to limit the vertical displacement is proportional to the vertical stiffness; the dynamic response of the track beam is negatively correlated with the transverse beam density of the main span track beam; and whether the main span is equipped with transverse beams has a greater impact on the vertical dynamic response of the suspended monorail vehicle and the bridge; with a lower vehicle speed, the transverse beam has a more obvious optimization on the vehicle lateral response, while with a higher vehicle speed, it will optimize the vehicle vertical response more obviously.